Hard-Anodized Aluminum Alloy: Wear Properties in Vegetable Oils - Chiara Soffritti; Annalisa Fortini; Enrico Baroni; Mattia Merlin; Gian Luca Garagnani (Lubricants)
The present study examines the tribological behavior of an EN AW-4006 aluminum alloy subjected to two innovative hard anodizing processes involving the sealing of anodic oxide pores with Ag+ ions and tested in lubricated conditions. Four plant-based lubricants with different concentrations of fatty acids were considered. Wear tests were conducted using a ball-on-disk tribometer, employing a constant frequency oscillatory motion at 2 Hz and a maximum linear speed of 0.1 m/s. The investigation explores the influence of applied loads (5 N, 10 N, and 15 N) on the resulting coefficient of friction. Through a Design of Experiments methodology, the most influential factors affecting the coefficient of friction are identified. The results indicate that hard anodizing processes and applied load affect the coefficient of friction during wear testing as the main factor of influence. High values of the Unsaturation Number led to a high coefficient of friction at 5 N. Wavy-shaped profile tracks were detected at 10 and 15 N, leading to high specific wear rate values and the failure of the anodized layer.